Вікові особливості структурних змін серця та стану ремоделювання міокарда у чоловіків із хронічною серцевою недостатністю на тлі надлишкової маси тіла та ожиріння - Бідзіля, Петро Петрович; Бидзиля, П. П.; Bidzilya, P. P. (My University, 2016)
Метою дослідження було вивчення особливостей структурних змін серця та стану ремоделювання міокарда у чоловіків із хронічною серцевою недостатністю на тлі надлишкової маси тіла та ожиріння. Результати дослідження. Виявлено, що чоловіки старечої вікової групи схильні до більш значної дилатації порожнин серця, мають тенденцію до поширення ексцентричного типу гіпертрофії та концентричного ремоделювання лівого шлуночка. Зі збільшенням віку відбувається наростання ступеня гіпертрофії лівого шлуночка, кальцинозу мітрального та аортального клапана з поширенням їх регургітації. Целью исследования было изучение особенностей структурных изменений сердца и состояния ремоделирования миокарда у мужчин с хронической сердечной недостаточностью на фоне избыточной массы тела и ожирения. Результаты исследования. Обнаружено, что мужчины старческой возрастной группы склонны к более значительной дилатации полостей сердца, имеют тенденцию к распространению эксцентрического типа гипертрофии и концентрического ремоделирования левого желудочка. С увеличением возраста происходит нарастание степени гипертрофии левого желудочка, кальциноза митрального и аортального клапана с распространением их регургитации. Introduction. Chronic heart failure is a relevant health, social and economic problem in Ukraine that becomes more common with aging. Overall, the prevalence of chronic heart failure in the general adult population is 1–2 % and in most cases is observed in older patients. Epidemiological studies demonstrated that the prevalence of disease in adult population ranges 1.5 to 5.5 %, increasing proportionately with age. At the age of over 70 years, the number of chronic heart failure cases reaches 5–10 %, and after 80 years it reaches 10–20 %. Age is a proven adverse factor of chronic heart failure; episodes of progression and mortality in older patients are more common as compared to the young. Among elderly patients, chronic heart failure is accompanied by 10–50 % one-year mortality, depending on the age of patients, the etiology of disease, ejection fraction of the left ventricle, the presence of atrial fibrillation and comorbid conditions. Progressive spread of chronic heart failure and obesity in the general population, issues regarding the details of structural changes of the heart, types of myocardial remodeling in men with CHF, the polarity of opinions concerning the influence of age, sex and concomitant obesity on the course and consequences of the disease determine the relevance of the chosen direction of research. Conclusion. Negative influence of age affecting the structural changes of heart and the state of myocardial remodeling in men with CHF secondary to overweight and obesity were demonstrated.
Возрастные особенности структурных изменений сердца и состояния ремоделирования миокарда у мужчин с хронической сердечной недостаточностью на фоне избыточной массы тела и ожирения
Age peculiarities of cardiac structural changes and the state of myocardial remodeling in men with chronic heart failure secondary to overweight and obesity
Keywords: серцева недостатність; чоловіки; надлишкова вага; ожиріння серця; ремоделювання; віковий фактор; сердечная недостаточность; мужчины; избыточный вес; ожирение; ремодрелирование сердца; возрастной фактор; heart failure; men; overweight; obesity; cardiac remodeling; age factor